Desarrollo de un gres porcelánico incorporando arcillas colombianas sometidas a un proceso de blanqueamiento (2020)
The objective of this work has been the development of porcelain stoneware pastes with raw materials of Colombian origin, with the same technical characteristics that currently have this type of products in the international context. For this purpose, different raw materials, including kaolinitic clays, feldspars and natural pozzolanas, have been studied from the central area of Colombia, specifically from the regions of Boyacá, Cundinamarca and Santander. Some of these raw materials have contents of iron oxide above 1% and have been subjected to both physical and chemical benefit processes in order to reduce the amount of this coloring oxide. The heap leaching method with oxalic acid has presented the best results, with a reduction in iron oxide content of 60 wt%. In this work a natural pozzolana of the Boyacá region has also been used, which has shown a greater fluxing and reactivity behavior, compared to national feldspar. In addition, the incorporation of fluxes such as nepheline and recycled glass has been studied. With these raw materials, porcelain stoneware compositions have been developed, obtaining water absorption values lower than 0,5%, in a temperature range between 1160°C and 1200°C.